2012
DOI: 10.4103/0972-0707.101914
|View full text |Cite
|
Sign up to set email alerts
|

The reinforcement effect of polyethylene fibre and composite impregnated glass fibre on fracture resistance of endodontically treated teeth: An in vitro study

Abstract: Aim:The aim of this study was to evaluate the fracture resistance of endodontically treated maxillary premolars with wide mesio-occluso-distal (MOD) cavities restored with either composite resin, or composite resin reinforced with different types of fibres. Materials and Methods:Fifty human maxillary premolars were selected. Five intact teeth served as positive controls. Endodontic therapy was carried out in the remaining forty-five teeth. Standardized MOD cavities were prepared in all the teeth. The teeth wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
1
18
0
1
Order By: Relevance
“…[ 1 ] Since, the 1990s fiber-reinforced posts have been employed more frequently to restore endodontically treated teeth that excessively lost tooth structure. Fiber reinforced posts (18-22 GPa) have a modulus of elasticity similar to the dentine (18 GPa);[ 2 ] they produce a stress field similar to that of natural teeth, thereby reducing the risk of root fractures[ 3 4 ] In addition, fiber posts showed increased incidence of repairable fracture when compared to cast dowel posts. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Since, the 1990s fiber-reinforced posts have been employed more frequently to restore endodontically treated teeth that excessively lost tooth structure. Fiber reinforced posts (18-22 GPa) have a modulus of elasticity similar to the dentine (18 GPa);[ 2 ] they produce a stress field similar to that of natural teeth, thereby reducing the risk of root fractures[ 3 4 ] In addition, fiber posts showed increased incidence of repairable fracture when compared to cast dowel posts. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…In another congruous study, Luthria et al , also evaluated the fracture resistance of ETT with wide MOD cavities restored with PFC resin reinforced by different types of FRCs (glass and polyethylene) ( 41 ). The results revealed that, the fracture resistance of composite restorations reinforced with glass FRCs (Interlig) was higher (600.5 N) than polyethylene FRCs (Ribbond) (514.6 N).…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that, the fracture resistance of composite restorations reinforced with glass FRCs (Interlig) was higher (600.5 N) than polyethylene FRCs (Ribbond) (514.6 N). Authors attributed the lower reinforcing efficiency of polyethylene FRC to the manually, non-uniform wetting of polyethylene FRC with unfilled resin, which negatively influenced on the adhesion of FRC to PFC resin matrix ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Though the use of composite resins for PERs has been routinely accepted, they are still not used in extensive restorations, especially in high stress-bearing areas, 60 as they have been shown to possess poor fracture resistance in all cavity designs. 61 This is due to the poor adhesive interface and bond strength, which is the lowest at the pulpal floor, followed by radicular dentin and the chamber wall.…”
Section: Posts a N D Core Materialsmentioning
confidence: 99%